A Case Report of Acute Transverse Myelitis Following Novel Coronavirus Infection - Deesha Sarma; Leslie A. Bilello (Clinical Practice and Cases in Emergency Medicine, 2020)
Introduction: During the coronavirus disease 2019 (COVID-19) pandemic, emergency providers are not only seeing an increasing number of patients with COVID-19 infections, but also associated complications and sequelae of this viral illness. Case Report: We present the case of a 28-year-old female patient who presented after a confirmed COVID-19 infection with lower back pain, bilateral symmetric upper and lower extremity numbness, and urinary retention. The patient was diagnosed with acute transverse myelitis. She required intravenous corticosteroids and plasma exchange with significant improvement in symptoms and minimal residual effects. Conclusion: This case illustrates the importance of prompt recognition and treatment of sequelae of COVID-19 infections.